FUNGSI PEMERINTAH DAERAH DALAM PENGELOLAAN PERTAMBANGAN DI KABUPATEN TRENGGALEK TAHUN 2015 - Su'adah, Yustafa Badrus (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2019)
One of the business activities that support development in Indonesia is the mining sector. The mining business is an activity to optimize the utilization of natural resources of mining or excavation material on land. Mining is part or all of the phases of operations in the research, management, and exploitation of minerals or coal covering general investigation, exploration, feasibility study, construction, mining, processing and refining, transportation and sales, and post-mining activities.